Impact assessment of public innovation support in European Economic Area - Vilys, Mantas; Jakubavičius, Artūras; Žemaitis, Eigirdas (Business, Management and Economics Engineering, 2015)
The object of this paper is related to the public innovation support in Euro-pean Economic Area and its effectiveness assessment. Main aim of the re-search presented in this paper is to propose new model for public innovation support effectiveness assessment, which could be relevant to the contempo-rary needs and would be based on new explored practice of public innova-tion support developments. The methods of comparative, regression, model-ling analysis, multi-criteria evaluation, analogy search, logical abstraction and impact evaluation have been applied for the research presented in this paper. Proposed original system of quantitative and qualitative indicators that characterize any public innovation support system (public innovation support index) enables creation and implementation of measures devoted to the public innovation support impact improvement at EU and national level.